Findings of Inclusive Education and Theater Pedagogy: curricular update for a Center of Comprehensive Care for People with Disabilities in Costa Rica - Rodríguez Ríos, Melissa (2020)
The present text sets out the objective of identifying the current training needs, as well as the pedagogical-administrative challenges and scopes, that implies the updating of the curriculum so that the theatrical pedagogy is integrated as a regular subject in the Association for Children and Exceptional Adults (APNAE), therefore, the current state of Inclusive Education and Artistic Education in Costa Rica is contextualized. Then, its expose the conceptual axes of the research, which give way to the construction of the analysis categories that are explained in the qualitative methodology, in which a participatory diagnosis was executed with the three study groups. The limitations of this research are that the institutional body (CONAPDIS, Department of Educational Supports for students with disabilities of the Ministry of Education, people or entities of Ministry of Culture and Youth) was not integrated as part of the research subjects due to a time limitation in the inquiry progress. Finally, it is concluded that the main pedagogical needs are: body-vocal language, gender and critical literacy. On the other hand, after the lack of articulation found between the public institutions in charge of ensuring the improvement of the educational center, it is recommended the creation of an Artistic Education Department in charge of ensuring the articulation of the different public institutional entities for the improvement of the statutes, regulations and curriculum of the APNAE, and in this way the theater pedagogy strategy is contemplated from a universal design.